Towards A Set Of Transformation Measurements Within A Community From An Organisational Change And Transformational Learning Perspective (2022)
ABSTRACT: Chapter 10 studies how a social organisation can trigger niche building by generating alliances between diverse stakeholders in cities. This chapter discusses how external forces (landscape shocks) influence niche development using analysis of social networks as an empirical approach.